On Competitive Strategy from OEM to OBM - A Case Study on a Sealing Parts Company in Taiwan - Chen, Jui-Lung; Hsieh, Chia-Chi (Journal of Asian business strategy, 2021)
As the market becomes more globalized and the international situation continues to undergo complex changes, the income and profits of the OEM business are getting thinner and smaller. In such circumstances, many companies have initiated OBM business, causing fierce brand competition in the market. This study took a sealing parts company in Taiwan as the subject to explore how the company operates smoothly to maximize profits with both OEM and OBM business, determines the proper business strategy according to different customer groups and market segments, distributes customer orders and develops business strategy when OEM business conflicts with OBM business, so as to avoid customer complaints and reduce the risk of losing orders. This study first discussed the brand positioning of the subject company and brand competitions in the industry. Next, through qualitative interviews, it analyzed the market segmentation under the competition among international brands and the impacts of COVID-19 on the development of company strategy.